Saving nature or nation in the Kachin Hills: an ethnography of encounters - Kiik, L (2020)
Amid decades of ethno-political war, northernmost Burma’s Kachin people have increasingly come into encounters with international projects for grabbing or saving local nature. Drawing on eighteen months of ethnographic fieldwork in 2017–2019, this thesis explores encounters between the Kachin ethno-national movement and outside-led projects of resource extraction and nature conservation. The thesis argues for ethnographic approaches that do not assume certain outcomes, but instead foreground diversely situated, contradictory, and empathic voices – both local and from outside – to explain why such encounters can lead to clash, collaboration, disconnect, or other pathways. The studied encounters showed many-sided disconnect, distrust, outreach, and collaboration amid war, driven by different sides’ comparable senses of emergency over saving natures or nations. Telling such stories of many-sided encounters can help anthropology in addressing analytical and ethical challenges when representing multi-scale conflict, conspiracy accusations, and ecological destruction.